Avant-garde in België 1917-1929. - Adriaens-Pannier, Anne; Buyck, Jean F.; De Wilde, Eliane; Leen, Frederik; Narmon, François; Pil, Eric; Schoonbaert, Lydia M. A., 1930-; Van Loo, Anne (Brussel : Museum voor Moderne Kunst Brussel, 1992)
Baugniet, Marcel-Louis ; Cockx, Jan ; Daenens, Albert ; De Boeck, Felix ; De Troyer, Prosper ; Donas, Marthe ; Eemans, Marc ; Flouquet, Pierre-Louis ; Gailliard, Jean-Jacques ; Jespers, Floris ; Jespers, Oscar ; Joostens, Paul ; Kiemeneij, Jan ; Leonard, Jos ; Maes, Karel ; Magritte, René ; Mesens, E.L.T. ; Peeters, Jozef ; Servranckx, Victor ; van den Berghe, Frits ; Van Dooren, Edmond ; Vantongerloo, Georges ; Wolfs, Hubert ; Baudoux, Yvan ; Bourgeois, Victor ; De Clerck, Oscar ; De Koninck, Louis-Herman ; Eggerickx, Jean-Jules ; François, Lucien ; Gaspard, Maurice ; Jasinski, Stanislas ; de Velde, Henry Van
biografie
Nederlands
boek
Keywords: interbellum; België